Homogenization of the zirconium carbide–titanium interface domain. (February 2016) - Pan, Rui; Wei, Hongmei; Lin, Tiesong; He, Peng; Sekulic, Dusan P.; Wang, Qiyue; Duan, Xiaoming
Abstract: An excellent homogenization of the ceramic (ZrC x )–metal (Ti) interface domain has been successfully achieved. A non-stoichiometric ZrC x under certain diffusion bonding conditions leads to a total consumption of the metal Ti interlayer, and to a formation of a homogeneous interface domain. The combined impact of a presence of carbon vacancies in zirconium carbide, and the mutual solubility between transition metal carbides, is instrumental in achieving the homogenization. This has, to the best knowledge of authors, never been reported. Graphical abstract: